Polish Inmigrants in Argentina - Zubrzycki, Bernarda (2012)
Argentina has always been among the nations with the largest percentage of immigrants and foreign residents, leading to a culture infused with elements from many nations. One of these is Poland, which sent more of its sons and daughters to Argentina than any other Latin American nation except Brazil. During most of the nineteenth century, immigrants from Poland were usually political exiles from the various revolutions intended to free the nation from forced occupation by its neighbors—Austria, Prussia and Russia. Among the first were veterans of Napoleon’s armies who had served the emperor in the vain hope that a French victory would result in recreation of an independent Poland. Given their military experience, some of these soon joined the forces of General José San Martín destined to liberate Argentina from its own colonial bonds. Foremost among them, according to the newspaper La Gaceta de Buenos Aires (The Buenos Aires Gazette) were Colonel General Antonio Belina-Skupieski, Lt. Antonio Mierz, Sergeant Major Juan Valerio Bulewski, and Corporal Miguel Zatocki, as well as many other enlisted men.